Prevalence of renal complications of levetiracetam in neonates with seizures in Qom from 2015 to 2020 - Saadati, Alireza; Akhavan Sepahi, Mohsen; Hassanvand Amouzadeh, Masoud; Hamta , Amir; Ahmadi , Shahab (Journal of Pediatric Nephrology, 2022)
Introduction: Spasms or seizures during the first month of life are the most common clinical manifestations of central nervous system failure in infants and occur due to overactivity of a group of nerve cells in the brain and excessive electrical stimulation of neurons. The purpose of the present study was to evaluate the prevalence of renal complications of Levetiracetam in neonates with seizures. Methods: This descriptive-analytical and retrospective study was performed on creatinine level, blood urea and duration of levetiracetam use for all neonates studied and only renal ultrasound was performed for cases where their creatinine was elevated. Finally, the obtained information was used for statistical analysis. Results: According to the results, there was no statistically significant differences in neonatal subgroups, especially in infants on levetiracetam, except transient increased creatinine and urea. During 6 months follow-up, only three cases with increased creatinine above 1.4 was observed. This 3 cases had normal genitourinary ultrasound. Also, in neonates diagnosed with choroid cyst on ultrasound, in one case the creatinine level was more than 1.4 and in the other cases the serum creatinine level was less than 1.4. Conclusion: According to the results of the present study, no serious renal complication was observed with Levetiracetam and its use can be recommended for patients.